The Structure And Long-Term Dynamics Of Competitive Activity Of Highly Qualified Basketball Players - Sardorkhan Kuvandikov; Ruxsora Ilxomjanova (Euro Asian Journal Publishing, 2024)
This article considers the competitive activities of basketball teams as a system, the components of which can be quantified and, subject to monitoring, will make it possible to optimize these indicators and sports results.
Keywords: competitive activity; system; system components